Assessing Changes in Knowledge and Practical Skills of Community Ambulance Volunteers Following Emergency Medical Training - Nur Chayati; Nur Hidayati; Azizah Khoiriyati; Esa Pradita Dazza; Toriqul Albab Firdaus (Carmin: Journal of Community Service, 2026)
The effectiveness of community-based ambulance services depends not only on ambulance availability but also on volunteers' capacity to recognize emergencies and ensure safe patient transport. This study examined the effect of emergency medical training on the knowledge and practical skills of community ambulance volunteers. A pre-experimental, one-group pretest-posttest design was employed involving 25 volunteers. The intervention comprised interactive lectures, demonstrations, simulation-based training, and hands-on practice addressing initial patient assessment, basic life support, first aid, and patient transfer techniques. Knowledge was measured before and after training using a validated questionnaire, while practical skills were assessed through direct observation using a standardized checklist derived from current resuscitation guidelines. Data were analyzed with a paired t-test. All participants were male, with a mean age of 43 years; most had completed senior high school, while the remainder held a bachelor's degree. Half had previously received emergency care training. Mean knowledge scores increased from 84.29 to 90.71 following the intervention, reflecting a 6.42-point (7.6%) improvement, though this change did not reach statistical significance (p = 0.082). Observational assessment indicated that most participants correctly performed the sequence of first aid interventions and patient transfer procedures. However, deficiencies persisted in specific psychomotor skills, including carotid pulse assessment, chest compression quality, and effective stretcher use, highlighting the need for continued practical training. Overall, emergency medical training demonstrated a favorable trend toward enhancing volunteers' knowledge and practical competencies in basic emergency care and safe patient transport. These findings suggest that simulation-enhanced training combined with interactive instruction can strengthen the capacity of community ambulance volunteers in prehospital emergency response. Regular refresher training and ongoing competency evaluation are recommended to sustain long-term knowledge retention and skill proficiency.